Analysis of Students' Mathematical Reflective Thinking Ability on Algebraic Forms Based on Discovery Learning Activities - Try Gita Cahyani; Demitra Demitra; Muhammad Rizaldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
The importance of reflective thinking skills in mathematics learning stems from in their demand for students to analyze, evaluate, and reconsider problem-solving strategies. The objectives of this study are: (1) to describe students' mathematical reflective thinking abilities based on discovery learning activities, and (2) to identify the factors that influence students' mathematical reflective thinking abilities. This study employed a mixed-method approach with an explanatory sequential design. Quantitative data were obtained through observations of the implementation of discovery learning, while qualitative data were gathered through tests and interviews with two students. The results show that students who effectively followed the stages of discovery learning tended to demonstrate a high level of mathematical reflective thinking. The research subjects were able to exhibit all three indicators of reflective thinking (reacting, comparing, and contemplating). Factors influencing students’ reflective thinking skills include cognitive aspects based on Bloom's taxonomy: knowledge (C1), comprehension (C2), application (C3), analysis (C4), and evaluation (C5).